Step
*
of Lemma
list_accum_equality
∀[T,A,B,C:Type]. ∀[f:A ⟶ T ⟶ A]. ∀[g:B ⟶ T ⟶ B]. ∀[F:A ⟶ C]. ∀[G:B ⟶ C].
∀[L:T List]. ∀[a0:A]. ∀[b0:B].
F[accumulate (with value a and list item x):
f[a;x]
over list:
L
with starting value:
a0)]
= G[accumulate (with value b and list item x):
g[b;x]
over list:
L
with starting value:
b0)]
∈ C
supposing F[a0] = G[b0] ∈ C
supposing ∀a:A. ∀b:B. ∀x:T. (((F a) = (G b) ∈ C)
⇒ (F[f[a;x]] = G[g[b;x]] ∈ C))
BY
{ (InductionOnList THEN Reduce 0 THEN Auto THEN RepeatFor 2 (BackThruSomeHyp) THEN Auto) }
Latex:
Latex:
\mforall{}[T,A,B,C:Type]. \mforall{}[f:A {}\mrightarrow{} T {}\mrightarrow{} A]. \mforall{}[g:B {}\mrightarrow{} T {}\mrightarrow{} B]. \mforall{}[F:A {}\mrightarrow{} C]. \mforall{}[G:B {}\mrightarrow{} C].
\mforall{}[L:T List]. \mforall{}[a0:A]. \mforall{}[b0:B].
F[accumulate (with value a and list item x):
f[a;x]
over list:
L
with starting value:
a0)]
= G[accumulate (with value b and list item x):
g[b;x]
over list:
L
with starting value:
b0)]
supposing F[a0] = G[b0]
supposing \mforall{}a:A. \mforall{}b:B. \mforall{}x:T. (((F a) = (G b)) {}\mRightarrow{} (F[f[a;x]] = G[g[b;x]]))
By
Latex:
(InductionOnList THEN Reduce 0 THEN Auto THEN RepeatFor 2 (BackThruSomeHyp) THEN Auto)
Home
Index